Online Learning Management System at SMPN 1 Rejang Lebong - Eva Susianti; Hamengkubuwono Hamengkubuwono; Muhammad Istan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Since the Coronavirus Disease (Covid-19) outbreak was announced as a pandemic by the WHO, it has certainly affected the face of education in Indonesia because of the implementation of social distancing so that learning is applied online. Schools are required to be able to implement online learning, including online learning management. This research is aimed at analyzing the implementation of online learning management based on the POSDCORB stages, and the implementation of online learning. This research uses a field research approach, and the subjects of this research are educators at the SMPN 1 Rejang Lebong who carry out online learning during the covid-19 pandemic and uses the method of observation, interviews, and documentation as data collection methods.This research shows that the teachers in SMPN 1 Rejang Lebong in implementing online learning management have carried out management stages. In this research, researchers examine the implementation of online learning management based on the management function of POSDCORB according to Luther Gulick's theory. Then the implementation of online learning at SMP Negeri 1 Rejang Lebong are: (1) Educators have a strategy of utilizing teaching time, then teachers also provide reinforcement and enrichment by using online media. (2) The teaching method used is a hybrid, namely collaboration between face-to-face learning and online learning methods. (3) The learning media used are electronic media and the use of online-based applications. (4) Learning evaluation, is a short-term learning evaluation, namely when online learning is carried out and when student assignments are collected.